Empowering Muslimah Students’ Awareness About Their Costume: Designing English Material For Islamic Higher Education - Widya Syafitri (HUMANISMA : Journal of Gender Studies, 2019)
Todays globalization has changed the lifestyle of Indonesian Muslim women, especially in college. Islamic values have been many abandoned by them. For example, we can see the ethics in dress and wear of hijab that has been far from Islamic sharia. As a speech says "Hijabi but naked". Many muslimah who use hijab but the beauty of body can still be seen by others. As if the use of hijab just follow the trend. The most feared thing is when the concept arises that the hijab is not an obligation for muslimah. To uncover this, as an educator, researchers feel obligated to bring back the muslimah students in accordance with the teachings of our prophet, Muhammad SAW. So this article designed the English materials about how to dress a muslimah based on Sunnah. This is development research, but focused on the design stage. The study resulted in the design of a valid English material after validated by the expert.